An Overview of Agro-Waste Management in Light of the Water-Energy-Waste Nexus - El-Ramady, Hassan; Brevik, Eric C.; Bayoumi, Yousry; Shalaby, Tarek A.; El-Mahrouk, Mohammed E.; Taha, Naglaa; Elbasiouny, Heba; Elbehiry, Fathy; Amer, Megahed; Abdalla, Neama; Prokisch, József; Solberg, Svein Ø.; et al. (Sustainability, 2022)
It is urgent that we increase global food production to support population growth. Food production requires significant resources, amongst them water and energy. Therefore, any losses of food or other agricultural products also means a waste of water and energy resources. A significant amount of these losses occurs during the postharvest stage, primarily during processing and storage. This is considered avoidable food waste. The water-energy-waste nexus (WEW), and its relationship to food production, needs to be investigated from a circular bioeconomy lens. Furthermore, alternative uses of the wastes should be investigated. This review focuses on agro-wastes and their management as sources for bioactive compounds, biofertilizers, biomaterials, nanomaterials, pharmaceuticals and medicinal agents, and growth media, e.g., for plant tissue culture. We also investigated the potential contribution of agro-wastes to bioenergy production (bioethanol, biogas, and biofuel). Proper management of agro-wastes may support the mitigation of climate change, produce innovative bio-ingredients and biodegradable materials, and enhance green growth and a circular bioeconomy. We argue that the management of agro-wastes cannot be discussed without referring to the role of water and energy within the food system. Thus, this review focuses on agricultural wastes and their handling, applications, environmental impacts, and potential benefits in the agricultural and medical industries in light of the WEW nexus.